(untitled) (Raparin Journal of Humanities (RJH), 2025)
Several critical theories have emerged throughout the history of literary criticism, evolving with the different stages and eras in which they developed. One such theory, reception theory, originated in response to the critiques of Russian constructivists and formalists. Established in the early 1970s by Hans-Robert Jauss and Wolfgang Iser, this theory emerged under particular circumstances in Germany and marked a significant shift in literary criticism by placing a strong emphasis on the role of the reader. The founders introduced numerous concepts and principles for analyzing literary texts, one of the foundational principles being the "horizon of expectations" put forward by Hans-Robert Jauss. This research focuses on analyzing the poem Sweetheart by (Hazervan Abdullah) through the lens of Jauss "horizon of expectations." It examines how the poem’s textual horizons influence and shape the reader’s reception, as well as how new horizons emerge during the act of interpretation. A literary text, particularly a new one, contains limitless horizons, offering diverse possibilities and perspectives to the reader. The significance of this research lies in its innovative approach, particularly in exploring the concept of "expectation" as a key principle in reception theory for analyzing intellectual poetry. In the poem Sweetheart, the poet employs numerous linguistic, structural, and artistic deviations, using them to disrupt the reader’s preconceived horizons, creating a sense of shock and transformation. These deviations allow the poet to exceed the reader’s expectations, prompting spontaneity, reflection, and change. As a result, the reader is not confined by the text or passively absorbed in it, but instead becomes an active participant in the reading process—deductive, productive, and driven to uncover alternative meanings within the text.